The Effectiveness of the Organization of Classes in Primary Classes Based on the Cluster Module (Journal of Pedagogical Inventions and Practices, 2022)
This research paper provides definitions of productive methods and technologies for the training of teaching staff in institutions of higher education, trends in the development of continuous professional education in general and teacher education in particular, and the educational tasks that arise from them that are relevant for the university